Altering the inhibitory kinetics and molecular conformation of maltase by Tangzhiqing (TZQ), a natural α-glucosidase inhibitor - Li, Yanfen (BMC Complement Med Ther, 2020)
BACKGROUND: Tangzhiqing (TZQ), as a potential α-glycosidase inhibitor, possesses postprandial hypoglycaemic effects on maltose in humans. The aim of this study was to investigate the mechanisms by which TZQ attenuates postprandial glucose by interrupting the activity of maltase, including inhibitory kinetics and circular dichroism studies. METHODS: In this study, we determined the inhibitory effect of TZQ on maltase by kinetic analysis to determine the IC(50) value and enzyme velocity studies and line weaver-burk plot generation to determine inhibition type. Acarbose was chosen as a standard control drug. After the interaction with TZQ and maltase, secondary structure analysis was conducted with a circular dichroism method. RESULTS: TZQ showed notable inhibition activity on maltase in a reversible and competitive manner with an IC(50) value of 1.67 ± 0.09 μg/ml, which was weaker than that of acarbose (IC(50) = 0.29 ± 0.01 μg/ml). The circular dichroism spectrum demonstrated that the binding of TZQ to maltase changed the conformation of maltase and varied with the concentration of TZQ in terms of the disappearance of β-sheets and an increase in the α-helix content of the enzyme, similar to acarbose. CONCLUSIONS: This work provides useful information for the inhibitory effect of TZQ on maltase. TZQ has the potential to be an α-glycosidase inhibitor for the prevention and treatment of prediabetes or mild diabetes mellitus.